The Role of Technology in Reforming Design Education - Jae-Eun Oh (Jap Sam Books, 2021)
Design education has significantly changed since the 1950s. The era depended widely on normative models such as those proposed by Benjamin Bloom (Bloom et al. 1956) and his collaborators, which resulted in the formulation of Bloom's Taxonomy. Comprising six interchangeable layers (knowledge, comprehension, application, analysis, synthesis, and evaluation) of higher and lower thinking, Bloom's taxonomy sets in place an archetypal model for education that thrives on object-driven goals. Here, pedagogical interchange and the object-driven and organised structure of education can adapt to each layer within the taxonomic structure.